Sex-dependent metabolism of ketamine and (2R, 6R)-hydroxynorketamine in mice and humans. (February 2022) - Highland, Jaclyn N; Farmer, Cristan A; Zanos, Panos; Lovett, Jacqueline; Zarate, Carlos A; Moaddel, Ruin; Gould, Todd D
Background: Ketamine is rapidly metabolized to norketamine and hydroxynorketamine (HNK) metabolites. In female mice, when compared to males, higher levels of ( 2R, 6R;2S, 6S )-HNK have been observed following ketamine treatment, and higher levels of ( 2R, 6R )-HNK following the direct administration of ( 2R, 6R )-HNK. Aim: The objective of this study was to evaluate the impact of sex in humans and mice, and gonadal hormones in mice on the metabolism of ketamine to form norketamine and HNKs and in the metabolism/elimination of ( 2R, 6R )-HNK. Methods: In CD-1 mice, we utilized gonadectomy to evaluate the role of circulating gonadal hormones in mediating sex-dependent differences in ketamine and ( 2R, 6R )-HNK metabolism. In humans (34 with treatment-resistant depression and 23 healthy controls) receiving an antidepressant dose of ketamine (0.5 mg/kg i.v. infusion over 40 min), we evaluated plasma levels of ketamine, norketamine, and HNKs. Results: In humans, plasma levels of ketamine and norketamine were higher in males than females, while ( 2R, 6R;2S, 6S )-HNK levels were not different. Following ketamine administration to mice (10 mg/kg i.p.), Cmax and total plasma concentrations of ketamine and norketamine were higher, and those of ( 2R, 6R;2S, 6S )-HNK were lower, in intact males compared to females. Direct ( 2R, 6R )-HNK administration (10 mg/kg i.p.) resulted in higher levels of ( 2R, 6R )-HNK in female mice. Ovariectomy did not alter ketamine metabolism in female mice, whereas orchidectomy recapitulated female pharmacokinetic differences in male mice, which was reversed with testosterone replacement. Conclusion: Sex is an important biological variable that influences the metabolism of ketamine and the HNKs, which may contribute to sex differences in therapeutic antidepressant efficacy or side effects.